The Role of Serum Amyloid A in Predicting Short Term Preterm Labor (Journal of Medical Sciences, 2022)
Background: preterm labour ( PL) is a major contributor to prenatal morbidity and mortality, defined by birth before completed 37 weeks of pregnancy. Not all cases with threatened PL end with labor; the reason is unclear. Many accredited infections as a cause for PL. We hypothesized that serum amyloid A (SAA), an acute-phase inflammatory reactant, may be used in predicting cases that proceed rapid PL. Material and methods: A prospective case-control study recruited 70 participants from the gynecology department of our University Hospital. All presented with threatened PL with intact membrane; in gestational age of 28-36 weeks of a singleton viable cephalic pregnancy. Detailed history and physical examination were made, and venous blood samples were aspirated and divided into two parts for CRP assessment and SAA estimation by ELIZA Kit. Patients were followed 31/70 delivered in 1 week times assigned as the study group, and the rest 39/70 were discharged home and continued pregnancy assigned as healthy controls. Results: Maternal serum SAA, CRP, and Gestational age were strongly significant as P